Comparative Utilization and Efficacy of Thrombopoietin Receptor Agonists in Relapsed/Refractory Immune Thrombocytopenia. (September 2021) - Arnall, Justin R.; DiSogra, Kristyn Y.; Downing, Lauren; Elmes, Joseph B.; Tran, Thuy; Moore, Donald C.
Abstract : Background: The thrombopoietin (TPO) agonists, eltrombopag and romiplostim, stimulate the production of platelets and offer an effective treatment option in relapsed/refractory immune thrombocytopenia (ITP). Recently published 2019 ITP guidelines recommend the TPO agonists as second-line therapy following corticosteroids; however, little data offer insights into comparative efficacy and tolerability. Study Question: Is there a difference in the efficacy between romiplostim and eltrombopag in relapsed/refractory ITP? Study Design: We conducted a single-center, retrospective chart review of patients with ITP treated with romiplostim or eltrombopag. Measures and Outcomes: The primary objective was a sustained platelet response, defined as platelets greater than 50, 000/μL in more than 66% of clinic visits over a 6-month period. Secondary objectives sought to evaluate response to and tolerability of TPO agonists. Results: The study included 107 consecutive patients, 67 (63%) on romiplostim and 40 (37%) on eltrombopag. Previous corticosteroids and rituximab were used in 95% and 50% of patients, respectively. There was no difference identified in platelet responses between the TPO-RAs, 72% romiplostim versus 65% eltrombopag ( P = 0.520). In addition, no differences were identified in secondary measures of response. Conclusions: In our experience with romiplostim and eltrombopag for ITP, we did not identify a difference in the efficacy of these agents. Further larger and prospective evaluations should be considered.